TEKNIK FUSING PADA DAUR ULANG LIMBAH KANTONG PLASTIK DAN IMPLEMENTASINYA PADA DESAIN PRODUK - Devanny Gumulya (Ide dan Dialog Desain Indonesia (Idealog), 2019)
Indonesia has become the second larget plastic waste contributor in the world after China. Saddens by this fact, this research is conducted to recycle plastic bag waste. Fusion technique is a technique to fuse two or more plastic plies by heating them. It is easily done because the equipment need is very easy to find. With fusion technique the plastic waste can be turned into durable and waterproof material. In this research, a card wallet is made out of the recycle material. Carry goods is a commodity that is continuously needed by market. The research used material driven design process, in which tries to explore the recycle material both in technical and experiential qualities. Aside from material exploration, this research also studiesabout user perception regarding this material, this study is needed to remove the waste stigma. From the study founded thatemotional and performative are affecting each other. The three traits that user about plastic fusing material are pattern, contras color and transparency. The results are design recommendation on how to design using this new material and functional products like wallet designed with different style that express the material uniqueness.